Konsep Tasawuf Al-Ghazali dan Kritiknya Terhadap Para Sufi (Telaah Deskriptif Analitis) - Mohammad Rohmanan (UPT Pusat Studi Aswaja UNISNU Jepara, 2021)
AbstractTasawwuf is one of the most valuable aspects of Islamic teachings. Al-Ghazali had a great influence on the world of Sufism and the Sufis. His thoughts are used as a reference by Muslim and non-Muslim scientists in the fields of psychology.. In this article, the author tries to discuss the concept of tasawwuf al-Ghazali and his criticisms of the Sufis. This research is a literature study with content analysis of the data that has been collected. The results of this study are: 1. al-Gh azali’s tasawwuf is a psychomoral tasawwuf which emphasizes moral development and purification of the soul; 2. Al-Ghazali's criticisms were aimed at Sufis who forgot or were far from the essence of Sufism itself.Keywords: al-Ghazali, Criticism, Islamic Psychology, Psychology, Sufi, Tasawwuf